Implementing recovery : a methodology for organisational change - Shepherd, Geoff; Boardman, Jed; Burns, Maurice (London : Centre for Mental Health, 2010)
Recovery describes the struggles of people with mental health problems to live meaningful and satisfying lives. The principles of recovery now underpin developments in mental health services in a number of countries. In England, they figure prominently in New Horizons and have received widespread support from the major professional bodies. This paper presents a practical methodology to help mental health services and their local partners become more recovery-oriented in their organisation and practices, and thereby to support these processes more effectively.
Keywords: Rehabilitation; Mental disorders